Mentoring Matters: An Innovative Approach to Infusing Mentorship in a Social Work Doctoral Program. (3rd April 2019) - Katz, Colleen Cary; Elsaesser, Caitlin; Klodnik, Vanessa Vorhies; Khare, Amy
ABSTRACT: Social work doctoral students must identify how to prioritize their time and how to gain the many qualifications required by the academic job market. Mentoring has long been recognized as an effective strategy for promoting academic success and degree completion in doctoral studies. This article describes three student-led initiatives in a social work doctoral program that sought to infuse mentorship throughout the program. The content of these innovative initiatives is discussed, as well as their implications for social work doctoral education.